Phase-Space Dynamics of Diatomic Molecules as Morse Oscillator - Adhikari, Dipak; Karki, Ravi; Adhikari, Kapil; Pantha, Nurapati; Adhikari, Narayan Prasad (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.